2021
DOI: 10.3389/fnhum.2021.606292
|View full text |Cite
|
Sign up to set email alerts
|

Right Temporoparietal Junction Plays a Role in the Modulation of Emotional Mimicry by Group Membership

Abstract: Our prior research demonstrated that the right temporoparietal junction (rTPJ) exerted a modulatory role in ingroup bias in emotional mimicry. In this study, two experiments were conducted to further explore whether the rTPJ is a neural region for emotional mimicry or for the modulation of emotional mimicry by group membership in a sham-controlled, double-blinded, between-subject design. Both experiments employed non-invasive transcranial direct current stimulation (tDCS) to temporarily change the cortical exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Our behavioral results showed that YG exhibited stronger subjective arousal and facial mimicry than the controls. The control group did not show any clear pattern of facial mimicry, which is consistent with previous findings that facial mimicry may be decreased in response to the faces of other races than to those of the same race ( 67 69 ). Regardless, YG demonstrated clear facial mimicry.…”
Section: Discussionsupporting
confidence: 91%
“…Our behavioral results showed that YG exhibited stronger subjective arousal and facial mimicry than the controls. The control group did not show any clear pattern of facial mimicry, which is consistent with previous findings that facial mimicry may be decreased in response to the faces of other races than to those of the same race ( 67 69 ). Regardless, YG demonstrated clear facial mimicry.…”
Section: Discussionsupporting
confidence: 91%
“…However, previous studies on emotional contagion do not focus on the importance of social context. Instead, they place greater emphasis on the characteristics of the expresser or receiver, such as eye orientation [15], face attractiveness [16], and so on, or on the relationship between the expresser and the receiver, such as intergroup relations [17,18]. As mentioned by Hess, social context is often excluded as an experimental distractor in these studies [9].…”
Section: Introductionmentioning
confidence: 99%